Pengaruh Faktor Individu, Organisasi dan Perilaku terhadap Kepatuhan Perawat dalam Melaksanakan Hand Hygiene di Ruang Rawat Inap Rumah Sakit Tk. II Dr. Soepraoen Malang - Fauzia, Neila; Ahsan (Jurnal Aplikasi Manajemen, 2014)
This study aims to determine the effect of individual, organization and behavior towards hand hygiene compliance of nurses. The research design used analytic descriptive study design with cross sectional approach on 71 respondents. Then, the researcher tested using descriptive statistical test, multiple linear regression analysis, hypothesis testing, and test the dominant variable. Individuals, organizations and behaviors significantly influence hand hygiene compliance of nurses. Individual variable dominantly influence on hand hygiene compliance of nurses.